DINAMIKA INTERAKSI SUKU TALANG MAMAK DI DESA TALANG PERIGI KECAMATAN RAKIT KULIM KABUPATEN INDRAGIRI HULU, RIAU - Bani, Bani; Zusmelia, Zusmelia; Anggreta, Dian Kurnia (Pendidikan Sosiologi, 2013)
Talang  Mamak  is  tradition  ethnic,  Langkat  Lama  ethnic  or  Talang    ethnic.  The  term  of Talang  ethnic means people who live in land and isolate  in the forest.  Seperated  residence system, commoly occupy in left side of river with small house or hut. The  research purposes to describe dynamics of  Talang Mamak  need fulfillment and describe the social interaction model  between  Talang  Mamak  ethnic  and  Malayan.  The  theory  used  in  this  research  is symbolik interaksionisme theory by  Herbert Blumer.  The  symbol that used in this research is symbolik  that  found  on  meaningful  materials  of  Talang  Mamak  ethnic  such  as  Bendul, Tonggap  and  also  Talang  Mamak  interaction  does  action  is  suitable  with  the  meaning. according  to  soekanto  social  interaction  model  consists  of  cooperation,  competation,  and conflict.  This  research uses descriptive tipe of qualitative approach.  Technique  of informan sorting done by using purposive sampling. Technique  of data collection in this research used obsevation,  intrview  and  documentation.  Data  analysis  done  in  the  research  by  using interactive  by  Miles  and  Huberman.  In  this  research  was  found  there  happened  food  need fulfillment dynamics where to fulfill food,  Talang Mamak provided by themself with moving field, but talang mamak donot do it anymore. talang mamak used clothes which also used bysociety  commonly  and  Talang  Mamak  do  not  use  clothes  made  from  leaf  or  cloth  (cawat) which only cover vital part of body. Then, Talang Mamak donot occupy in the forest but live at the edge of road.  Interaction  model that happrned between  Talang Mamak and  Malayan is cooperation in rubber sale,  honey sale, cleaning worship place, and marriage tradition.  Other interaction model happened between Talang Mamak and Malayan is threat conflict.